The Relationship between Social Support and Suicidal Ideation Among College Students: A Moderated Mediation Model - Chen, Youqin; Ni, Na (Journal of Contemporary Medical Practice, 2024)
Objective: To investigate the relationship and its mechanism between social support and suicidal ideation among college students. Methods: A total of 530 college students were surveyed using the Social Support Rating Scale, Beck Suicidal Ideation Scale, Self-Control Scale and Reasons for Living Inventory for Adolescents. Results: (1) Self-control was a mediating variable between social support and suicidal ideation, with an effect value of -0.80, accounting for 37.91% of the total effect; (2) Reasons for living moderated the second half of the mediating effect of self-control (β = 0.436, t = 3.647, P < 0.003). Conclusion: Social support influences suicidal ideation through the mediating role of self-control and the moderating role of reasons for living.